2005
DOI: 10.1038/sj.gt.3302498
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-mediated delivery of TIMP-3 plasmid DNA into saphenous vein leads to increased lumen size in a porcine interposition graft model

Abstract: Progressive saphenous vein graft (SVG) narrowing and occlusion remains a major limitation of coronary artery bypass grafting and is an important target for gene therapy. Ex vivo adenoviral gene transfer of tissue inhibitor of metalloproteinase 3 (TIMP-3) reduces adverse SVG remodelling postarterialization, but concerns remain over the use of viral vectors in patients. Ultrasound exposure (USE) in the presence of echocontrast microbubbles (ECM) substantially enhances nonviral gene delivery. We investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…Indeed, we found that ex vivo transfection of saphenous vein segments using ultrasound yielded only 50-fold enhancements compared with the 3000-fold effects of ultrasound upon vascular smooth muscle cell transfection in vitro. 4 However, in vivo transfection is always less efficient than in vitro and several of the studies in Table 1 also report that the maximum efficiency of UEGT was similar to or better than viral or liposome-mediated transfection. Transgene expression post UEGT is transient, certainly when using standard promoters such as cytomegalovirus, generally peaking at 4-7 days and with rare exceptions is essentially gone by 21 days.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, we found that ex vivo transfection of saphenous vein segments using ultrasound yielded only 50-fold enhancements compared with the 3000-fold effects of ultrasound upon vascular smooth muscle cell transfection in vitro. 4 However, in vivo transfection is always less efficient than in vitro and several of the studies in Table 1 also report that the maximum efficiency of UEGT was similar to or better than viral or liposome-mediated transfection. Transgene expression post UEGT is transient, certainly when using standard promoters such as cytomegalovirus, generally peaking at 4-7 days and with rare exceptions is essentially gone by 21 days.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 99%
“…Table 2 summarizes some recent examples using animal models and therapeutic transgenes that have potential clinical relevance. 4,37,55,56,69,70 Although these and other in vivo studies provide proofof-concept that UEGT can indeed achieve therapeutically effective gene transfer, the delivery approaches used (e.g. direct injection of plasmid/MCB into the liver or left ventricular cavity, UEGT requiring temporary cessation of blood flow in target organs) are in many cases unattractive for clinical use, certainly if repeat administrations for chronic conditions are contemplated.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 99%
See 2 more Smart Citations
“…These qualities mean that BR14 may be a better agent in sonoporation-mediated transfection. Indeed, recent studies have indicated that BR14 effectively enhanced sonoporation-based gene transfection into hepatic cancer implant in mice [21] as well as into saphenous vein graft in porcine [22].…”
mentioning
confidence: 99%